'Interception': a model for specialist prehospital care provision when helicopters are not available. Issue 11 (4th September 2013) - McQueen, Carl; Apps, Richard; Mason, Fay; Crombie, Nicholas; Hulme, Jon
Abstract : The deployment of specialist teams to incident scenes by helicopter and the delivery of critical care interventions such as Rapid Sequence Induction of anaesthesia to patients are becoming well-established components of trauma care in the UK. Traditionally in the UK, Helicopter Emergency Medical Services (HEMS) are limited to daylight operations only. The safety and feasibility of operating HEMS services at night is a topic of debate currently in the UK HEMS community. Within the West Midlands Major Trauma Network, the Medical Emergency Response Incident Team (MERIT) provides a physician-led prehospital care service that responds to incidents by air during daylight hours and by Rapid Response Vehicle during the hours of darkness. The MERIT service is coordinated and supported by a dedicated Major Trauma Desk manned by a HEMS paramedic in the ambulance service control room. This case illustrates the importance of coordination and integration of specialist resources within a major trauma network to ensure the expedient delivery of HEMS-level care to patients outside of normal flying hours.